Genetic Diversity in Jatropha curcas L. Assessed with SSR and SNP Markers - Juan M. Montes; Frank Technow; Matthias Martin; Klaus Becker (Diversity, 2014)
Jatropha curcas L. (jatropha) is an undomesticated plant that has recently received great attention for its utilization in biofuel production, rehabilitation of wasteland, and rural development. Knowledge of genetic diversity and marker-trait associations is urgently needed for the design of breeding strategies. The main goal of this study was to assess the genetic structure and diversity in jatropha germplasm with co-dominant markers (Simple Sequence Repeats (SSR) and Single Nucleotide Polymorphism (SNP) in a diverse, worldwide, germplasm panel of 70 accessions. We found a high level of homozygosis in the germplasm that does not correspond to the purely outcrossing mating system assumed to be present in jatropha. We hypothesize that the prevalent mating system of jatropha comprise a high level of self-fertilization and that the outcrossing rate is low. Genetic diversity in accessions from Central America and Mexico was higher than in accession from Africa, Asia, and South America. We identified makers associated with the presence of phorbol esters. We think that the utilization of molecular markers in breeding of jatropha will significantly accelerate the development of improved cultivars.